L'efficacité de l'expertise maritime amiable - Delaubier, Clara (Aix-Marseille Université, 2022)
La situation de l’expertise maritime amiable facultés peut être résumée par le constat suivant : bien qu’elle ne soit pas réglementée, elle est, dans le cadre des contrats d’assurances facultés, quasi-systématiquement prévue. La résolution de ce paradoxe réside dans l’efficacité de cette institution, forgée par sa pratique historique. Cette efficacité est fondée sur des caractéristiques, tenant d’abord à l’expert mais impactant également la réalisation de l’expertise. Sur la base des critères que doit présenter l’expert, à savoir la compétence et l’indépendance, les parties impliquées dans la négociation du contrat d’assurance facultés élaborent une liste d’experts agréés pour intervenir, en particulier, en cas de dommage. Néanmoins, ce choix ne lie pas les parties, les modalités devant présenter une certaine flexibilité afin de correspondre aux exigences du commerce international, dont le transport maritime est le vecteur principal. Par ailleurs, l’expertise doit être réalisée de manière méthodique et contradictoire afin de faire émerger la vérité factuelle du dommage et du sinistre et donc de pouvoir utilement remplir sa fonction principale, qui est probatoire. En tout état de cause, l’efficacité de l’expertise reste limitée, notamment au regard de la valeur probatoire que certaines juridictions françaises accordent au rapport d’expertise amiable, appelant des évolutions de l’expertise maritime ainsi qu’une amélioration des fondements de son efficience
Keywords: Adversary system; Assessment; Assurances facultés; Assurances maritimes; Cargo insurance; Commerce international; Competence; Compétence; Contradictory; Cotradictoire; Damage; Dommage; Efficacité; Efficiency; Evidence; Expert's survey; Expertise amiable; Expertises maritimes; Experts d'assurances; Facts; Fait; Independance; Indépendance; International trading; Loss; Probatory value; Proficiency; Self-Sufficiency; Sinistre; Survey report; Transports maritimes; Valeur probatoire

The legal framework for multimodal transport in West Africa: the African Continental Free Trade Area in perspective - Osinuga, Damilola (World Maritime University, 2022)
This thesis examines how multimodal transport can play a role in achieving the objectives of the African Continental Free Trade Area (AfCFTA). The thesis argues that multimodal transport is cheaper compared with unimodal transportation. While there are a number of issues affecting the operationalisation of multimodal transport in Africa, this study considers, at its core, the legal regimes and other fragmented institutional and governance frameworks of multimodal transport in West Africa. The fragmentation of the legal framework governing multimodal transport leads to uncertainty and unforeseeability of the liability of parties involved in multimodal transport, consequently leading to increased legal costs. There is an undisputed view that for effective regional integration, which Africa is seeking to achieve through the establishment of the African Continental Free Trade Area, there is a need to eliminate all trade barriers. Trade barriers (tariff or non-tariff barriers) should be removed to improve competitiveness and reduce trade friction costs. In other words, to achieve the objectives of the African Continental Free Trade Area, it is essential that all unnecessary costs associated with trade are eliminated or reduced to the barest minimum. The process of doing this is called trade facilitation. This thesis looks at the impact of trade facilitation on regional integration and trade. This thesis’ original contribution to knowledge is that Africa’s regional integration process needs cost-effective transportation in order to achieve smooth market access, and multimodal transportation can provide the most cost-effective solution. However, the legal uncertainty and complexities that could potentially ensue from the use of multimodal transport make it unattractive to prospective users. Accordingly, actions must be taken to reduce legal ambiguity and create a system in which liability is foreseeable and predictable. This study reveals that the current legal framework is incomplete, unsatisfactory and, ultimately, leads to uncertainty. The thesis further contends that neither the option of freedom of contract nor improving the current system of various Economic Community of West African States (ECOWAS )member-states’ view of multimodal transport, can significantly improve the current fragmented system or deliver the needed certainty. Accordingly, the thesis proposes that a modified uniform system would help achieve the legal certainty needed for multimodal transport. The thesis finally submits that the ECOWAS should establish a legally binding, regional governance regime on multimodal transport and a majority of its member-states should ratify the instrument.

Multimodal taşıma operatörünün sorumluluğu - Alhan, Yunus (Akdeniz Üniversitesi, 2022)
Multimodal taşıma; multimodal taşıma sözleşmesine binaen multimodal taşıma operatörünün eşyaların bir yerden farklı yerdeki teslimat için belirlenmiş bir noktaya taşınmasını en az iki farklı taşıma türü ile gerçekleştirmeyi taahhüt ettiği bir taşımadır. Konteyner kullanımının yaygınlaşması, günümüzde uluslararası eşya taşımalarının birden fazla taşıma türü kullanılarak kapıdan kapıya şeklinde yapılmasına olanak sağlamıştır. Bu sayede multimodal taşıma tüm dünyada yaygın hale gelmiştir. Taşıma sektöründe sıklıkla kullanılan bu taşıma türünün hukuki açıdan izahı önem arz etmektedir. Bu sebeple, multimodal taşımanın tanımı ve unsurları ele alınmıştır. Bu taşımanın diğer taşıma türleri ile benzerlik ve farklıkları değerlendirilmiştir. Her bir taşıma türüne ilişkin konvansiyonlar, ülkelerin ulusal hukuk düzenlemeleri ve multimodal taşımaya ilişkin yeknesak kurallar oluşturma amacıyla getirilen düzenleme çalışmaları ve düzenlemeler göz önüne alındığında multimodal taşımaya hangi hukuk düzenlemelerinin uygulanacağını öngörmek zordur. Multimodal taşımalarda sorumluluğu yeknesaklaştırmak adına en önemli düzenlemeler 1975 ve 1992 tarihli Milletlerarası Ticaret Odası (ICC) Kuralları ve halen yürürlüğe girmemiş olan 1980 Tarihli Multimodal Taşıma Konvansiyonu (MTC), 2009 tarihinde imzaya açılan Eşyaların Tamamen veya Kısmen Deniz Yoluyla Uluslararası Taşınmasına İlişkin Konvansiyondur (Rotterdam Kuralları-RK). Bu düzenlemelerden esinlenilerek ortaya çıkmış çeşitli bölgesel düzenlemeler söz konusudur. Bunun yanı sıra multimodal taşımanın ülke sınırları içerisinde gerçekleşebilmesi sebebiyle bazı ülkeler bu konuyu düzenleyen kanunlar yapmışlardır. Türk Hukunda ise multimodal taşımaya ilk kez 6102 sayılı Türk Ticaret Kanunu'nda (TTK), 'Değişik Tür Araçlar İle Taşıma' başlığı altında yer verilmiştir. MTO'nun zıya, hasar ve geç teslime dayalı sözleşme kaynaklı sorumluluğu zarar yerinin belirlenebilir olup olmamasına göre farklı kurallara tabidir. Zarar yerinin belirlenmesi ve multimodal taşıma sözleşmesinin taraflarından birinin zararın hangi taşıma türünde oluştuğunu ispatlaması durumunda, multimodal taşıma birden fazla taşıma türünü içerdiğinden denizyolu, havayolu, karayolu, demiryolu ve ülke iç suyolu gibi her bir taşıma türünü ayrı ayrı düzenleyen ve her biri kendi sorumluluk rejimini içeren uluslararası unimodal (tekil) taşıma konvansiyonlarından usulüne göre yürürlüğe girmiş olanları öncelikli olmak üzere, ilgili taşıma türünü özel olarak düzenleyen kurallar uygulanacaktır. Zararın gerçekleştiği taşıma türünün tespit edilememesi durumunda genel hüküm olarak adlandırabileceğimiz TTK hükümleri uygulama alanı bulacaktır. Çalışmada, Türk Hukukunda MTO'nun sorumluluğu ilgili konvansiyonlar ve TTK ışığında ele alınmış, uygulanacak hükümler ortaya konmaya çalışılmıştır. Anahtar Kelimeler: Multimodal Taşıma, Multimodal Taşıma Sözleşmesi, Multimodal Taşıma Operatörü, Multimodal Taşıma Operatörünün Sorumluluğu. Multimodal transport is a carriage in which multimodal transport operator, who assumes the responsibility of performing the carriage under the multimodal transport contract, undertakes to perform the carriage of goods by at least two modes of transport from one place to another place designated for delivery. Widespread use of containers today allows international transport of goods to be in the form of door-to-door transport using more than one mode of transport. Thus, multimodal transport becomes more widespread all over the world. Explaining this mode of transport, which is frequently used in the transport industry, from the legal perspective is of high importance. Hence, in this study, the definition and elements of multimodal transport are studied. The similarities and differences of this mode of transport with other modes of transport are evaluated. Considering different conventions regulating each mode of transport, national transport legislations and regulations aimed at setting forth uniform provisions, it is clearly difficult to determine rules that are applicable for the multimodal transport contract. Major regulations to uniform the liability in multimodal carriages are the 1975 and 1992 International Chamber of Commerce Rules, the 1980 Multimodal Transport Convention (MTC) and the United Nations Convention on Contracts for the International Carriage of Goods Wholly or Partly by Sea (Rotterdam Rules-RT), which was open for signature in 2009. There are also regional regulations inspired by these instruments. In addition, a number of countries enact laws regulating multimodal transport, as multimodal transport may be performed within national boundaries, and there are no uniform rules regulating it. In Turkish law, certain rules on multimodal transport in the Turkish Commercial Law (TTK) No.6102 under the heading of 'Carriage by Various Modes of Transport (Multimodal Transport)' were introduced. The MTO's contractual liability for loss of or damage to goods or delay in delivery is subject to different rules depending on whether the place of loss can be located. If the place of loss is located, and the leg of transport in which the loss occurs is proved by any party of the multimodal transport contract, as the transport involves more than one mode of transport, rules specifically regulating that mode of transport, in particular unimodal conventions, which duly entered into effect, individually governing each mode of transport such as sea, air, road, rail and inland waterway transports and having its own liability regime, will be applicable. If the mode of transport in which the loss occurs cannot be ascertained, TTK provisions, which we may call general rules, will be applicable. In the present study, we analyse the liability of MTO within the framework of relevant conventions and TTK and seek to reveal applicable provisions. Keywords: Multimodal Transport, Multimodal Transport Contract Multimodal Transport Operator, Liability of Multimodal Transport Operator
Keywords: Carrier's responsibility; Contract of carriage; Multimodal taşımacılık; Multimodal transport; Taşıma sorumluluğu; Taşıma sözleşmesi; Taşımacılık; Transportation; Turkish Commercial Code; Turkish commercial law; Türk Ticaret Kanunu; Türk ticaret hukuku

Navlun sözleşmesinde gönderilenin sorumluluğu - Arslan, Zeynep (Kocaeli Üniversitesi, 2022)
Deniz ticaret hukukunda, varma limanında yükün teslimini talep eden kişi, gönderilen olarak tanımlanmaktadır. Gönderilen, navlun sözleşmesinin tarafı olan taşıtan olabileceği gibi sözleşme ilişkisi dışında üçüncü bir kişi de olabilir. Gönderilenin üçüncü kişi olması hâlinde navlun sözleşmesi üçüncü kişi yararına sözleşme olarak nitelendirilmektedir. Kanun koyucu, sözleşme ilişkisine taraf olmayan bu üçüncü kişi için de bir takım hak ve sorumluluklar getirmiştir. İşte bu çalışmanın konusunu üçüncü kişi sıfatını haiz gönderilenin navlun sözleşmesinden kaynaklanan sorumluluğu oluşturmaktadır. Sözleşmelerin nispiliği prensibi gereği kural olarak tarafların anlaşarak üçüncü kişiyi borç altına sokmaları mümkün değildir. Bununla birlikte üçüncü kişi gönderilenin hangi hallerde sorumlu olacağı TTK m. 1203'te düzenlenmiştir. Buna göre gönderilenin navlun sözleşmesi kapsamında sorumlu olması için ilk olarak eşyanın teslimini talep etmesi gerekmektedir. Eşyanın teslimini talep, üçüncü kişi lehine sözleşme teorisi açısından edimin kabulü olarak değerlendirilmekte ve haliyle gönderilenin borç altına girmesi tarafların kararlaştırması ile değil öncelikle kendi iradesi ile olmaktadır. Gönderilenin sorumlu tutulmasının diğer şartını, teslim talebinin dayandığı taşıma sözleşmesinde ya da deniz taşıma senetlerinde bu borçların gönderilen üzerine bırakılması oluşturmaktadır. Dolayısıyla gönderilenin yükün teslimi sözleşmeden ya da deniz taşıma senetlerinden kaynaklanan bu alacakların ödenmesi şartına bağlanmaktadır. Gönderilenin hangi alacaklardan sorumlu olduğu sözleşme şartlarına göre tespit edilmektedir. Bu kapsamda sözleşme kayıtlarının incelenmesi gerekir. Navlun sözleşmesinde gönderilen uygulamada genellikle denizaşırı alıcı olarak karşımıza çıkmaktadır. Dolayısıyla Incoterms uyarınca tarafların kararlaştırdığı teslim şekillerinin ve FIO/FIOST/FILO/LIFO gibi gönderilenin sorumluluğunu genişleten kayıtların incelenmesi önemlidir. Bu kapsamda gönderilenin navlun sözleşmesinden kaynaklanan hangi borç kalemlerinden sorumlu olduğu sözleşme hükümleri ve mevzuat ile ayrıntılı bir şekilde açıklanmıştır. The consignee is defined as a person who requesting the delivery of the cargo at the discharge port by the maritime commercial law. The consignee might be the shipper, as a party of contract of affreightment, or might be a third party of the contract. In the case of the consignee is a third party, the contract of affreightment is characterized as a third-party beneficiary contract in which determined rights and responsibilities are given to this third party by the law makers. This thesis aims to determine the responsibilities of the third-party consignee that arising from the contract of affreightment. With regard to privity of the contract principle, as a rule, parties of a contract do not have right to bind a third party with obligations. On the other hand, the conditions of responsibilities of the third party consignee is regulated in the article 1203 of TCC. With regard to the article, in order for the consignee to be liable under the freight contract, the consignee must first request the delivery of the goods. The demand for the delivery of the goods is considered as the acceptance of the performance in terms of the theory of third party beneficiary contract and as a matter of fact, the consignee do not incur a debt with the parties' decision, but primarily with his own will. The other condition of holding the consignee responsible is the transfer of these debts to the consignee in the contract of affreightment or other transport documents on which the delivery request is based. Therefore, the delivery of the cargo is subject to the payment of these debts arising from the contract or transport documents. The debts of the consignee are determined according to the terms of the contract. In this context, it is necessary to review of the terms of the contract. In practice, the consignee in the contract of affreightment usually appears as a overseas receiver of the sale contract. Therefore, it is important to examine both the delivery methods agreed by the parties with regard to INCOTERMS and clauses that expand the responsibility of the sender, such as FIO/FIOST/FILO/LIFO. In this framework, this study explains in detail the responsibilities of consignee with regard to freight contract provisions and legislations.
Tez N°740401
Keywords: Commercial law; Contracts of affreightments; Deniz hukuku; Droit maritime; Freight; Gönderenin sorumluluğu; Law of the sea; Navlun; Navlun sözleşmeleri; Responsibility; Responsibility attiribution; Senders responsibility; Sorumluluk; Sorumluluk yükleme; Sözleşmeler; Ticaret hukuku

La responsabilité civile du transporteur maritime des hydrocarbures pour faits de pollution - Madani, Ahmed (Université Abou Bekr Belkaid, 2022)
Keywords: Hydrocarbure; Pollution; Responsabilité civile; Transport maritime; Transporteur maritime

Airport Charges Regulation: A Private Law Approach - Mei, Di (McGill University, 2022)
This thesis explores the regulation of airport charges, which is an important but marginalised topic. It particularly examines how private law instruments can play a role in the regulatory process. Airports used to be subject to traditional regulation, which operates in a command-and-control mode. As the airport industry becomes increasingly complicated, traditional regulation seems problematic. First, the method that is associated with traditional regulation to draw a line between regulated and unregulated airports has downsides. Second, the international regulatory framework on airport charges lacks binding rules. This suggests that traditional regulation is not the best niche for airport charges regulation. Third, good regulation needs independent regulatory bodies, which are hard to achieve in practice.In this context, this thesis argues that a private law approach can serve as a more flexible and effective way to regulate airport charges. There are two instruments under this overarching approach. First, contracts can be adopted to incorporate airport charges regulations. Second, robust corporate governance generates the effect of good regulation. This is an interdisciplinary work that has engaged air law, contract law, corporate law, competition law, and aviation business and management. It also employs the method of case studies. Chapter 4 examines the regulation of airport charges in the UK, Canada, and India. The three case studies demonstrate that private law instruments have been implicitly implemented to different degrees in these countries. These demonstrate the feasibility of applying private ordering in the regulatory process. I also look into the regulation of countries and regions including Australia, Ireland, the EU, and Germany throughout this thesis. This study also examines a specific sector of airport charges, namely, charges for ground-handling services. This sector possesses a unique feature in that it is between aeronautical and non-aeronautical services. A private law approach can also be adopted in the regulation of charges relating to ground-handling services. Additionally, ICAO as an important international organisation governing international air transport can also contribute to a private law approach of airport charges through its soft-law making function. This thesis aims to shed light on a private law approach, as an innovative regulatory mechanism, to airport charges. That said, regulation by this approach and traditional regulation are not contradictory but can cooperate to an extent, depending on how much power one wants to give to private ordering
Identifier: https://escholarship.mcgill.ca/concern/theses/8910k0504
Keywords: Airport; Regulation

Kara eşya taşıma sözleşmelerinde taşıyıcıya teslimin hukuki sonuçları - Sar, Mustafa Seyfullah (İstanbul Ticaret Üniversitesi, 2022)
Mesafe ve sınırların ortadan kalkmasıyla uluslararası ticarette pozitif yönde ivme kazanılmıştır. Bu yolda uluslararası ekonomik ilişkilerin geliştirilmesi amacıyla yapılan anlaşmalar, kurulan örgütler, sağlanan teşvikler ve kaldırılan ithalat vergileri sayesinde, farklı ülkelerdeki firmalar ve bireyler, birbirleriyle daha hızlı bir şekilde alışverişe girmeye başlamış ve bunun sonucunda ticari faaliyetler ülke sınırlarını aşarak küresel boyutlara ulaşmıştır. Bunun sağlanabilmesi için taşıma sektöründe kullanılan araçlar detaylandırılarak daha güçlü hale getirilmiştir. Böylelikle malların dağıtımı daha ekonomik, güvenli ve hızlı bir şekilde gerçekleştirilmektedir. Bunun sonucu olarak taşıma sözleşmelerinin uluslararası ticaretteki yeri de giderek önem kazanmıştır. Öyle ki hakların ve borçların teminatı için sözleşme kaçınılmaz yoldur. Yakın tarihte, uluslararası alanda ticaretin daha kolay ve hızlı hale getirilmesi için yeknesak bir sistem oluşturulması ihtiyacı ortaya çıkmış ve buna binaen ulusal düzenlememiz olan TTK'nın yanında, uluslararası karayolu taşımacılığında, koşulları standardize eden, taşıyıcının sorumluluklarını belirleyen CMR Konvansiyonu oluşturulmuştur. Düzenlenen kurallar doğrultusunda, taşıyıcı eşyayı teslim aldığı andan teslim edinceye kadar zarardan ve kayıptan sorumlu olacaktır. Taşıyıcı, ancak TTK ve CMR'de yer alan genel ve özel kurtuluş karinelerinin varlığının ispatı halinde sorumluluktan muaf olabilecektir. Aksi halde taşıyıcı, meydana gelen zarar veya zayiatın oranı doğrultusunda sorumlu olacak ve buna müteakiben tazminat miktarı belirlenecektir. TTK ve CMR pek çok noktada benzerlik gösterse de bazı yönleriyle keskin farklılıklar mevcuttur. Uluslararası ticaretin bekası için önem oluşturan bu nokta özellikle sorumluluk hususunda hukuki tartışmaları da beraberinde getirmiştir. With the obstacle of distances and borders disappearing, international trade has gained speed in a positive direction. Thanks to deals and agreements that were made, organisations that were built, incentives that were provided, and removal of import taxes in order to improve economic relations with this respect, companies and people in different countries have started to be able merchandise with each other more quickly; consequently, tradal actions have crossed borders of lands and reached global level. For this to happen, vehicles used in the sector of transportation have been developed, thus made stronger and more elaborate. As a result of this, the distribution of goods can be ensured in a more economic, safer, and faster way, and the role of vehicle contracts in international trade has gradually gained importance as contracts are inevitable to ensure and guarantee rights and debts. In recent history, a need to have a uniform system that would enable international trade to be easier and faster was born, and consequently, in addition to our regulations on TTK (Turkish Commercial Code), CMR Convention which standardized conditions and determined the responsibilities that transporters have in international land transportation. According to the regulations, the transporters are responsible for the safety of the goods in case of a damage and loss) from the moment they take them until they deliver them. The transporters can only be exempt from this responsibility in the case that general and specific presumptions of innocence that a place in the law (TTK) and the CMR can be proven. Otherwise, the transporter shall be responsible for compensating for the damage or the loss that occurred and the cost for the indemnity shall be determined. Although TTK and CMR Convention have similarities in many regards, in some ways they are distinctively different from one another. This point which has a critical role in the future of international trade has brought about many juridical discussions, especially ones related to responsibilities.
728226
Keywords: Contracts; Delivery; Eşya taşıma; Goods transportation; Highway Route with International Furniture Removal Agrement; Highway transportation; Kara yolu taşımacılığı; Karayolu ile Uluslararası Eşya Taşıma Sözleşmesi; Obligation to delivery; Sözleşmeler; Teslim borcu; Teslimat; Turkish Commercial Code; Turkish commercial law; Türk Ticaret Kanunu; Türk ticaret hukuku